Comparativo entre gordura hidrogenada de soja e oleína de palma durante processo de fritura em escala industrial - Silva, Juliana Arantes (2020)
Continuous immersion frying is an industrial food preparation process that takes place in oil or fat under high temperature. This cooking process has advantages for its speed, feasibility and develops pleasant sensory characteristics in the food. Inappropriate use during the frying process, oils and fats become more susceptible to degradation reactions, becoming responsible for the sensory and nutritional quality of the fried food. The objective of the work was to determine the composition in fatty acids, quality physical-chemical parameters and characterization of volatile compounds by solid phase microextraction (SPME) in static headspace and gas chromatography in samples of hydrogenated vegetable fat and refined palm olein, used in the industrial frying process of meat products in different frying cycles. The quality control analyzes that were performed on the frying fats were the acidity, peroxide, iodine, p-anisidine indices, total oxidation value, as well as the specific extinction by absorption in the ultraviolet region. These analyzes are necessary because they are related to the sensory and nutritional characteristics of fried foods. The major fatty acids in unused fats were palmitic, oleic and linoleic acids, with 38,65%, 45,17%, 10,07% and for the hydrogenated vegetable fat of 11,70%, 36,99%, 20,81%, respectively. In the fats submitted to the frying cycles, the levels of palmitic, oleic and linoleic acids reached in the refined palm olein a value of 39,77%, 45,21%, 10,01% and for the hydrogenated vegetable fat of 12,30%, 38,74%, 20,86%, respectively. Trans fatty acids were identified in the hydrogenated vegetable fat without use in both batches, 14,62% and 21,23%. The results of the acidity and peroxide indexes found in the samples were in accordance with the Brazilian legislation in force. The total oxidation value (totox) reached, after frying, a maximum of 59.22 in refined palm olein and 60.13 in hydrogenated vegetable fat. The fats were analyzed by spectroscopy in the ultraviolet and medium infrared regions, making it possible to monitor the oxidation process and identify spectral bands such as the presence of carbonyl groups, and cis and trans isomers for the purpose of evaluating the quality of the fats. Regarding volatile compounds, the highest percentage in the fats that have not yet gone through the frying process was 2- 4-decadienal and the compound formed in greater quantity was acrolein. The results indicate that the reuse of fat during an extended frying cycle leads to unwanted decomposition. Therefore, these analyzes are important to assess the quality and characteristics of the oils and fats used during the industrial frying process. In relation to the comparison between the two fats, refined palm olein suffered less decomposition, therefore, in terms of oxidation, this would be the ideal fat to be used during the industrial frying cycle.